A review on bilayer tablets of multi drug combination of anti-retro viral drugs - Patil Sagar N; Shailesh Sharma (International Journal of Pharmacy and Analytical Research, 2017)
Multilayer tablets are novel drug delivery systems where combination of two or more drugs in a single unit having different release profiles which improves patient compliance, prolongs the drug(s) action. Bilayer tablets are prepared with one layer of drug for immediate release while second layer designed to release drug, later, either as second dose or in an extended release manner. Trilayer tablets are prepared with one layer of drug for immediate release while second and third layers designed to release drug, later, either as second dose or in an extended release manner. These Multilayer tablets are suitable for sequential release of two or more drugs in combination, separate incompatible substances, and also for sustained release tablet in which one layer is immediate release as initial dose and second layer is maintenance dose. Acquired immune deficiency syndrome epidemic is one of the greatest challenging facing the medical community today. Combination of three drugs commonly used in the management of the Human Immunodeficiency Virus (HIV) infection. Zidovudine (AZT), the first anti‐HIV compound approved for the clinical use is widely used for treatment of AIDS either alone or in combination with other antiviral agents and Zidovudine is water soluble and soluble at all pH ranges and absorbs throughout the gastrointestinal tract and so sustained release tablet is better approach than the conventional dosage form. Lamivudine is a potent antiviral agent used in the treatment of AIDS. Lamivudine is a potent nucleoside analog reverse transcriptase inhibitor. Lamivudine is rapidly absorbed with a bioavailability of over 80% following oral ingestion. Lamivudine are administered multiple times a day because of its moderate half-life of 5 to 7 hours. Tenofovir disoproxil is an antiretroviral medication used to prevent and treat HIV/AIDS and to treat chronic hepatitis B. The active substance is tenofovir, while tenofovir disoproxil is a prodrug that is used because of its better absorption in the gut.